Bio-responsive composite liposomes against Campylobacter jejuni in vitro and its application in chicken preservation. (October 2022) - Lin, Lin; Mei, Canchao; Chen, Xiaochen; Li, Changzhu; Hua, Zichun; Cui, Haiying
Abstract: The infection of Campylobacter jejuni ( C. jejuni ) in food can cause huge economic and health costs, and liposomes based on biological switch is a promising antibacterial strategy. In this study, a bio-responsive composite liposome was designed with silk fibroin and L-fucose (FLPs) based on the chemotaxis and protease of C. jejuni, and Litsea cubeba essential oil as antibacterial agent. The oil encapsulation and protein mosaic rates of the composite liposome were 70.6 ± 0.5% and 47.9 ± 1.0%, respectively. The in vitro release experiment verified that the release rates of essential oil from the liposome exceeded 95% at 5 days. Furthermore, FLPs possessed excellent antibacterial activity, the inhibition zone was 23.5 mm and 20% ( v /v) of the composite liposomes could inactivate 99% C. jejuni . Moreover, laser scanning confocal microscopy and scanning electron microscopy images confirmed the antimicrobial activity of FLPs was better than that of other liposomes, and it could attach to bacteria well. Sprayed liposomes revealed sustained ability of retarding bacterial reproduction within 5 days with the refrigerated chicken meat inoculated with C. jejuni, and had no impact on the color and texture of the food. Hence, the bio-responsive composite liposome has a promising application in inhibiting C. jejuni growth in food. Industrial relevance: In this study, the composite liposome with high encapsulation efficiency shows significant and sustained antibacterial activity, and has no negative effects on the color and texture of chicken meat. The findings of this study will facilitate the development and application of liposomes as active antimicrobial packaging in food industry. Highlights: 20% (v/v) of the composite liposomes could inactivate 99% Campylobacter jejuni ( C. jejuni ). Stimulated release was proved by co-culture of composite liposomes and C. jejuni . C. jejuni population in chicken was 4.43 log CFU/g on the 5th day after liposomes spraying. The prepared liposomes (0.2 mL) has no impact on the color and texture of chicken breast meat.